2020
DOI: 10.3390/ijerph17030881
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Trace Element Contamination Using Ficus macrophylla Leaves in Urban Environment

Abstract: Urban areas are characterized by numerous pollutants emitted by anthropic sources both in the form of solid and gaseous particulates. Biomonitoring is an easy, economical, and accessible approach for the determination of atmospheric pollutants. In this study, we used the leaves of Ficus macrophylla Desf. ex Pers., collected in the city of Palermo (Italy), to determine major and trace elements. Geogenic elements exhibited the highest concentrations, making up 99% of the weight of the analyzed elements (Ca, K, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
(74 reference statements)
2
3
2
Order By: Relevance
“…The lack of variation in Pb concentration between the four plant species may possibly be due to their stationary nature or form, which makes them easily exposed and vulnerable to the equal amount of Pb dust being released into the atmosphere from mining sites. On average, Ficus plants had a very high Pb concentration, which agrees with Alaimo [60], who confirmed that Ficus macrophylla leaves are suitable for screening an urban environment to identify concentrations of inorganic chemicals due to their high tolerance to pollution. On the contrary, previous studies by Ombugadu, et al [23] showed that Mangifera indica accumulated Pb the most, while Ficus platyphylla had the least amount of Pb.…”
Section: Areassupporting
confidence: 84%
“…The lack of variation in Pb concentration between the four plant species may possibly be due to their stationary nature or form, which makes them easily exposed and vulnerable to the equal amount of Pb dust being released into the atmosphere from mining sites. On average, Ficus plants had a very high Pb concentration, which agrees with Alaimo [60], who confirmed that Ficus macrophylla leaves are suitable for screening an urban environment to identify concentrations of inorganic chemicals due to their high tolerance to pollution. On the contrary, previous studies by Ombugadu, et al [23] showed that Mangifera indica accumulated Pb the most, while Ficus platyphylla had the least amount of Pb.…”
Section: Areassupporting
confidence: 84%
“…pallasiana (Lamb) Holmboe, sampled at various distances from the Tuncbilek Thermal Power Plant (Kütahya Province, Turkey). They were lower than those recorded by Alaimo and Varrica (2020) for unwashed leaves of Ficus macrophylla collected in the city of Palermo (Italy); concentrations ranged between 16 and 99 µg/g, and than those reported by Fazrul and Huda (2018) for the leaves of Athyrium esculentum (18.5 ± 1.83 µg/g), Chromolaena odorata (23.35 ± 2.89 µg/g), and Lantana camara (26.85 ± 0.77 µg/g) taken from a roadside in the Jengka sub-urban area in Pahang, Malaysia. Nevertheless, concentrations recorded for washed and unwashed leaves of F. retusa were largely higher than those reported by Alahabadi et al (2017) for unwashed leaves of Robinia pseudoacacia (4.45 ± 1.83 µg/g), Pinus eldarica (3.08 ± 1.35 µg/g), Olea europaea (3.56 ± 1.68 µg/g), and Cupressus arizonica (3.23 ± 1.23 µg/g) sampled in the urban area of Yazd in Iran.…”
Section: Plant Parts Hms Contentscontrasting
confidence: 63%
“…xed at (100 µg/g) by Allen et al (1974), and Yilmaz and Zengin (2004). Comparison of zinc concentrations in the study area and those recorded in cities around the world, showed that our results were extremely higher than those recorded by Alaimo and Varrica (2020) for unwashed leaves of F. macrophylla collected in the urban area of Palermo (Italy); concentrations ranged from 14.5 to 31 µg/g, and those reported by Alahabadi et al (2017) for unwashed leaves of Robinia pseudoacacia (27.2 ± 14.29 µg/g), Pinus eldarica (33.25 ± 7.45 µg/g), Olea europaea (27.23 ± 14.42 µg/g), and Cupressus arizonica (26.1 ± 6.08 µg/g) sampled in the urban area of Yazd in Iran. They were in the range of those recorded by Abou El Saadat et al ( 2011) for leaves of F. retusa sampled in a sub-urban (40.03 µg/g), urban (67.39 µg/g) and industrial areas (76.31 µg/g).…”
Section: Plant Parts Hms Contentscontrasting
confidence: 53%
“…Desert dust is capable of traveling long distances in the atmosphere [12]. In addition to affecting air quality, desert dust also has broader impacts on climate and biogeochemistry [13][14][15]. As mentioned, North Africa alone contributes significantly to global dust emissions (55%).…”
Section: Introductionmentioning
confidence: 99%